Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/bdrc.20182
|View full text |Cite
|
Sign up to set email alerts
|

Extending the family table: Insights from beyond vertebrates into the regulation of embryonic development by FGFs

Abstract: Since the discovery of Fibroblast Growth Factors much focus has been placed on elucidating the roles for each vertebrate FGF ligand, receptor, and regulating molecules in the context of vertebrate development, human disorders and cancer. Studies in human, mouse, Xenopus, chick, and zebrafish have gone a long way to help us understand [AS1]which FGFs are involved in which processes. However, in recent years, as more genomes are sequenced, more information is becoming available from many non-vertebrate models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 141 publications
0
22
0
Order By: Relevance
“…Keeping FGF signaling properly regulated is important for normal ovary development, but its exact role in supporting gonad development is unclear. Furthermore, FGF signaling is conserved as its biological roles and structural properties appear similar in Drosophila and higher vertebrates (Huang and Stern, 2005; Tulin and Stathopoulos, 2010b). Studies of how FGF signaling impacts Drosophila ovary morphogenesis have the potential to provide novel insights into conserved functions and/or regulatory mechanisms acting in other organisms, including vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping FGF signaling properly regulated is important for normal ovary development, but its exact role in supporting gonad development is unclear. Furthermore, FGF signaling is conserved as its biological roles and structural properties appear similar in Drosophila and higher vertebrates (Huang and Stern, 2005; Tulin and Stathopoulos, 2010b). Studies of how FGF signaling impacts Drosophila ovary morphogenesis have the potential to provide novel insights into conserved functions and/or regulatory mechanisms acting in other organisms, including vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies in vertebrate systems postulate that heterodimeric FGF ligand combinations do activate FGFRs and structural studies of FGF-FGFR interactions support this view (Plotnikov et al, 2000;Zhang et al, 2006), to our knowledge, no definitive experimental evidence exists. Over 120 FGF-FGFR interactions are presumed to function in vertebrates (Zhang et al, 2006), whereas evidence for activity of three combinations has been presented in Drosophila (Kadam et al, 2009;Tulin and Stathopoulos, 2010). Here, taking advantage of this simplified receptor-ligand system in Drosophila, we studied the differential effects of multiple FGF ligands in activating the same FGFR receptor and how this contributes to symmetric and synchronous migration of CVM cells.…”
Section: Introductionmentioning
confidence: 99%
“…A fifth Fgfr-like protein (FgfrL1) has also been identified that lacks an intracellular tyrosine kinase domain and likely negatively regulates Fgfrs by sequestering ligand (for review, see Trueb et al 2013). Fgf signaling is required throughout metazoans and is commonly studied in organisms ranging from cnidarians to humans (Tulin and Stathopoulos 2010). These studies indicate that Fgf signaling is required pleiotropically during development and also regulates multiple homeostatic and reparative functions in adults (Ornitz and Itoh 2015).…”
mentioning
confidence: 99%